PENGARUH DEBT TO EQUITY RATIO, PRICE BOOK VALUE, PRICE EARNING RATIO, DAN RETURN ON ASSET TERHADAP RETURN SAHAM PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rispantyo, Putri Ayu Kusumaningrum, Bambang Widarno & (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The purpose of this study was to analyze: 1) effect of the debt to equity ratio on stock returns 2) effect of price to book value of the stock return 3) effect of price earning ratio on stock returns 4) effect of return on assets on stock returns. This research is an empirical study. The study population is a food and beverage company listed on the Indonesia Stock Exchange. Sampling techniques used purposive sampling with a sample of 14 companies. Source data used secondary data from website www.idx.co.id. Methods of data collection used documentation and literature study data were analyzed using classical assumption test and multiple linear regression analysis. The results showed that the debt to equity ratio (DER) has negative and significant effect on stock returns. Price book value (PBV) has positive and significant effect on stock returns. Price earnings ratio (PER) has positive and significant effect on stock returns. Return on assets (ROA) has negative but no significant effect on stock returnKeywords: debt to equity ratio, pricebook value, priceearnings ratio, return on assets and stock returns